Common Sense and Cultural Hegemony in Ram Shekhar Nakarmi’s Pa:khaa - Maharjan, Rubee (Shahid Kirti Multidisciplinary Journal, 2025)
Caste system, in Nepal, has helped maintain a definite social structure. In contrast, the system also created a social barrier separating ‘higher’ and ‘lower’ castes. However, so called ‘lower caste’ are considered lawfully equal in all the accesses since more than a decade. Nevertheless, unavoidable prejudices still exist in the society regarding identities and capabilities of these ‘outcasts’. So, this paper is an endeavor to identify such causes through the content analysis of Ram Shekhar Nakarmi directed Newari movie, Pa:khaa (literally meaning, the wall), released in 2012. In this article, I have analyzed the representation of the status of the protagonist, her failure to redeem herself from the destitution and the state of her being an outcast in the primary text under scrutiny . In this attempt, I have tried to examine traces of resistance against ‘cultural hegemony’ and finally inferred that ‘common sense’, which is the manifestation of ‘cultural hegemony’, is indeed a powerful tool that infuses in the both the higher and lower caste people and letting the barrier of caste discrimination pertain in the communities. I have analyzed the primary text by applying the basic theoretical framework envisioned by Antonio Gramsci’s notion of cultural hegemony.